Experiences of Discrimination and Sexual Behaviors: An Examination of Motives as Potential Psychological Mediators. Issue 2 (3rd April 2019) - Hagiwara, Nao; Grollman, Eric A.; Green, Tiffany L.
Abstract: Objectives : We investigated three psychological mechanisms that may underlie the associations between discrimination and sexual activity: emotion regulation, autonomy restoration, and intimacy building. Methods : An online survey was administered to a diverse sample of 565 undergraduate students at a large public university. Results : Having sex to mitigate negative emotions mediated the associations between self-reported discrimination and lifetime number of sexual partners, and between discrimination and the frequency of sexual intercourse while intoxicated. Conclusions : Sexual activity may serve as a coping strategy in response to the experiences of negative emotions and human core needs thwarted by the experiences of discrimination.